Utilization of Humorous Text in the Instagram Account @ngakak.tiap.hari as Indonesian Language Learning - Windo Dicky Irawan; Masitoh Masitoh; Irawan Suprapto (Journal of Research in Social Science and Humanities, 2024)
Humorous language is very necessary in forming emotions and interactions among teachers and students. Humor provides a positive side in the form of a more pleasant atmosphere and causes laughter. The aim is to eliminate boredom or tension in the classroom through humor. Based on researchers' observations, humorous language is often considered not to be important in the learning process at school. In fact, to form emotions and interactions that are not rigid in students, it is necessary to use humorous language. This research aims to (1) describe humorous texts in the Instagram account @ngakak.tiap.hari. (2) use of humorous texts as teaching materials for learning Indonesian. The data used in this research is humorous text on the Instagram account @ngakak.tiap.hari, while the data source used in this research is fifteen posts on the Instagram account @ngakak.tiap.hari. which contains humorous text. The data collection used in this research was the listening and note-taking method. The data analysis technique related to this research uses pragmatic matching and referential matching methods with the technique of selecting determining elements. The validity of the data in research uses theoretical triangulation.